Effects of co-exposure to arsenic and dichlorvos on glutathione metabolism, neurological, hepatic variables and tissue histopathology in rats. Issue 1 (16th August 2013) - Flora, S. J. S.; Dwivedi, Nidhi; Deb, Utsab; Kushwaha, Pramod; Lomash, Vinay
Graphical Abstract: Abstract: The individual toxic effects of arsenic and organophosphate pesticides are known but there is a lack of data on their combined effects. The present study investigates the toxic effects following combined exposure to organophosphate and arsenic on: (i) alterations in brain biogenic amines, (ii) oxidative stress and its correlation with glutathione linked enzymes, cell death and histopathological observations, and (iii) arsenic concentration in soft tissues. Rats were exposed to arsenic (1 mg kg −1 body weight, orally) and dichlorvos (4 mg kg −1 body weight, subcutaneously) either individually or in combination for 16 weeks. Arsenic alone and in combination with DDVP led to a significant increase in reactive oxygen species (ROS), thiobarbituric acid reactive substance (TBARS), glutathione peroxidase (GPx) and glutathione- S -transferase (GST) activities accompanied by a decreased glutathione reductase, reduced and oxidized glutathione (GSH and GSSG) levels in tissues. Arsenic and DDVP also produced a significant depletion in brain biogenic amines; however, acetylcholinesterase (AChE) activity increased moderately on arsenic exposure. Arsenic and DDVP co-exposure exhibited synergism in the case of ROS while no such effect was noted in the case of TBARS. Interestingly, combined exposure to arsenic and DDVP resulted in more pronounced toxic effects compared to their individual effects based on various biochemical variables, cell death (TUNEL assay) and histopathological observations. Interestingly, brain arsenic levels decreased on co-exposure to arsenic and DDVP accompanied with prominent elevation of liver arsenic content in co-exposed groups. The present study thus provides some interesting observations on the interaction between arsenic and DDVP including (i) co-exposure to arsenic and DDVP might lead to significant oxidative stress and (ii) their co-exposure produced synergistic effects on some liver variables but some antagonistic effects on the brain.